Understanding Emotional Engagement Amongst Primary School Children for Designing Gamification in Learning - Ahmad Rizal Ahmad Rodzuan; Azlina Ahmad; Nazlena Mohamad Ali; A. Imran Nordin (2018)
Student engagement is an essential element for students to perform well in their studies. This paper focuses on one specific type of student engagement called the emotional engagement. The aim is to investigate whether student’s emotional engagement influences their academic performance. In addition, this paper explores how gamification can be used to help educators to increase student’s emotional engagement in learning. In this study, we measure student’s emotional engagement level based on their academic performance. We also recorded their feedback on gamification elements that they prefer during the lesson. The outcome indicates that there is no significant effect of emotional engagement on student performance. We argue that this could be caused by the instrument used in the study. The instrument is widely used by the western researchers, and its implementation in the Asian settings such as in Malaysia could be different due to the local values, principles, syllabus and the education system. However, the students responded well on some of the gamification elements, showing a positive direction for us to apply gamification technique in the classroom. More work is needed to be done to identify factors that can enhance student’s emotional engagement in learning, as well as to explore the benefits of gamification in learning.